Governing cities for sustainable energy: The UK case. (May 2016) - Webb, Janette; Hawkey, David; Tingey, Margaret
Abstract: The dependence of cities on intensive consumption of energy from fossil fuels is a major cause of climate disruption, and there is increasing interest in the potential for city governments to facilitate a transition to sustainable energy. Little is known, however, about the extent or structures of current urban energy initiatives. Our paper addresses this gap by mapping UK local authority energy plans and project investments and exploring governance processes in three leading cities. It uses socio-technical and urban studies' perspectives on neo-liberal governing and energy systems to interpret findings. This reveals both the gap between local ambitions and capacity to implement plans, and the potential for translation of neo-liberal governing into contrasting commercial and community urban energy enterprises, prefiguring different energy futures. Overall, however, the neo-liberal framework is associated with small scale and uneven initiatives, with limited contribution to a systemic shift to sustainable cities. Highlights: Three quarters of UK local authorities show ambition in local energy governing. Activity is most evident in decentralised energy and efficiency retrofit. Case studies contrast community and commercial local energy governing. Projects are small scale with limited contributions to a low carbon urban system. We conclude neo-liberal governing limits municipal capacity for sustainable energy.